Crisis and neoliberal counter-reforms - García, Guillermo (Nómadas. Critical Journal of Social and Juridical Science, 2012)
The recent financial crisis in the rich countries has brought out the predictable, but irresponsibly neglected consequences of excessive financial speculation by private banks and transnational corporations. Colluding with many statesman and political leaders, these banks and corporations have prevented their own collapse by expropriating substantial resources from the sector they consider "obsolete" -the public sector, ignoring the failure of the measures enhancing the private sector that they have imposed and keep imposing according to one of the mottos of the neo-liberal globalization: "governance". In this way they are ensuring the continuity of the forms of neo-colonial domination all over the planet.